ENT 530 Business Plan : Flamz Shoz Sdn Bhd / Mohamad Zailani Sapari ... [et al.] - Sapari, Mohamad Zailani; Zulkiply, Amira Farhana; S.Ramli, Anis Najiha; Muhammad Zaini, Norshazlin Ashikin; Mukhtar Affandi, Siti Nur Farhana (2019)
Flamz Shoz Sdn Bhd offers shoe products and services for customers, providing the variety types of design and colour based on customer needs that will gives high satisfaction of consumer. Our clients is customers identifying as student, working adults and tourist which include both gender, men and women who want to consume product with affordable price of product. We also targeting busiest workers because we have online seller of our product to customers home.